Optimization of intermediate anchors to eliminate premature shear failure of CFRP laminate flexurally strengthened R.C beams - Jumaat, Mohd Zamin; Alam, M.A. (International Journal of Physical Sciences, 2011)
Flexurally strengthened RC beams usually fail by means of premature shear due to low shear as compared to flexure. Intermediate anchors in the length of shear span of those beams would successfully eliminate this problem. This paper presents the experimental studies on the effects of intermediate anchors in preventing premature shear failure of CFRP laminate flexurally strengthened RC beams. Design guidelines to optimize the intermediate anchors for eliminating premature shear failure are proposed. In the experimental programme, four RC beams were cast. One beam was tested in the un-strengthened condition to act as the control beam. The remaining beams were strengthened with CFRP laminates. Among the strengthened beams, one beam was prepared without intermediate anchors, one was intermediate anchored based on the proposed design method, and the last one was intermediate anchored using arbitrary anchor plates. Results showed that strengthened beam with having optimal intermediate anchors had higher ultimate strength as compared to that of the control beam. The optimal anchors significantly increased both the ultimate load as well as ductility of the said beams as compared to the beam without intermediate anchors. Moreover, the optimal intermediate anchors also reduced the number of cracks and crack widths in the shear span region. In conclusion, the beam with optimal intermediate anchors had identical failure load, crack widths, deflections and strain characteristics as that of arbitrarily anchored strengthened beam.